2011
DOI: 10.1111/j.1423-0410.2011.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the studies of bleeding complications of platelets pathogen‐reduced with the Intercept system

Abstract: Treatment with Intercept may increase the risk of all and clinically significant (albeit not severe) bleeding complications in RCTs maintaining a platelet count of ≥10×10(9) or ≥20×10(9)/l through increased platelet transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 55 publications
1
49
3
1
Order By: Relevance
“…Results obtained with one method cannot be extrapolated to those obtained by other methods. In the first published meta-analysis that included the HOVON trial, Vamvkas concluded that there was a clinically significant increase in mild and moderate bleeding complications in the arm receiving treated-platelets [85]. However, this meta-analysis contained a serious methodological bias: it combined the results of clinical studies of amotosalem/UVA with the results of a clinical study of riboflavin/broad spectrum UV.…”
Section: Clinical Studiesmentioning
confidence: 95%
“…Results obtained with one method cannot be extrapolated to those obtained by other methods. In the first published meta-analysis that included the HOVON trial, Vamvkas concluded that there was a clinically significant increase in mild and moderate bleeding complications in the arm receiving treated-platelets [85]. However, this meta-analysis contained a serious methodological bias: it combined the results of clinical studies of amotosalem/UVA with the results of a clinical study of riboflavin/broad spectrum UV.…”
Section: Clinical Studiesmentioning
confidence: 95%
“…The ongoing scientific dispute about the clinical effectiveness of PI-PCs indicated a potentially limited acceptance of the new components by the clinicians. Lower corrected count increments for PI-PCs compared to conventional PCs (cPCs) with unclear clinical significance were reported by meta-analyses [9,10]. Additionally, acute respiratory distress syndrome (ARDS) was described in significantly more patients having received PI-PCs (5/328) than in those transfused with cPCs (0/327 [11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis evaluated the outcome of clinical bleeding across five published randomized controlled trials (RCTs) in INTERCEPT and non‐PI PLT recipients . This meta‐analysis is a revision of a previous meta‐analysis by the same author in the past year, using additional data, including only the INTERCEPT technology and using somewhat different criteria for RCT inclusion and data analysis.…”
Section: Risks Incurred With Implementation Of Intercept Apsmentioning
confidence: 99%
“…The results for clinically significant bleeding (defined as at least Grade 2 bleeding by one of two standardized bleeding measurement scales used in the different studies) varied depending upon which of two US SPRINT trial data sets (per‐protocol bleeding events or bleeding events from AE reporting, which involved a slightly longer observation period) was used. Using per‐protocol data, there was no difference (odds ratio [OR], 1.24; 95% CI, 0.79‐1.93), whereas using AE data, clinically significant bleeding in INTERCEPT recipients was increased by 50% (OR, 1.52; 95% CI, 1.09‐2.12) . As has been pointed out, daily per‐protocol bleeding assessment using WHO criteria is a more objective and accurate tool than is spontaneous hemorrhagic AE data obtained by untrained personnel as part of global adverse event (AE) monitoring.…”
Section: Risks Incurred With Implementation Of Intercept Apsmentioning
confidence: 99%